Development of Large-Scale Farming Policies - Nammontri, Rattanaphorn; Katekao, Viporn; Nimpanich, Jumpol; Chokprajakchart, Srisombat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This article aims to study the development of large-scale farming policies: A case study of the Sam Bundit large-scale farming group community enterprises. Sam Bundit Subdistrict, Uthai District, Phra Nakhon Si Ayutthaya Province. This study used a documentary research and in-depth interviews with 6 members of the large-scale farming Community Enterprise Group. The results of the study revealed that the development of large-scale farming policies consisted of 1. Develop and promote farmers to become Smart Farmers. 2. Promote government personnel to have knowledge and expertise in the policy. 3. Increase research and development of rice seeds. 4. Develop an irrigation system to cover all areas. 5. Develop a wireless network system 6. Determine the process of creating a new body of knowledge to have a clear direction in accordance with the development mechanism for driving large-scale farming policies to help farmers reduce costs Increase efficiency and develop sustainable rice quality. 7. Set clear directions on the need for technology to be used in production. 8. Give importance to soil and water ecosystems.